Penelitian Tindakan Kelas (PTK) bagi Guru SD Inpres Perumnas Antang I Kota Makassar - Sirajuddin Saleh; Haerul Haerul (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The main problem faced by the partners is not yet agood understanding of the concept of action research (CAR),the Partners cannot distinguish between types of classroomaction research with other research, and partners do notunderstand the procedures for the preparation of classroomaction research report. Therefore, in order to overcome theproblems mentioned above, the proposed solution is to conducttraining and guidance to partners on research, class actions,particularly in the preparation of classroom action researchreport. The training is expected to produce a systematic formatof writing/preparation of reports Classroom Action Research(CAR), and teachers who have been trained (partners) have theskills/understanding in preparing classroom action researchreport.